2018
DOI: 10.1111/cdev.13192
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Perinatal and Concurrent Anxiety and Mental Health Problems in Early Childhood: A Sibling‐Comparison Study

Abstract: Do associations between maternal anxiety symptoms and offspring mental health remain after comparing differentially exposed siblings? Participants were 17,724 offspring siblings and 11,553 mothers from the Norwegian Mother and Child Cohort study. Mothers reported anxiety and depressive symptoms at 30 weeks’ gestation, and 0.5, 1.5, 3, and 5 years postpartum. Child internalizing and externalizing problems were assessed at ages 1.5, 3, and 5, and modeled using multilevel analyses with repeated measures nested wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 59 publications
2
29
0
1
Order By: Relevance
“…Fourth, it is possible that the associations between maternal depressive symptoms and child emotional and behavioral problems could be partly explained by various prenatal influences, such as maternal prenatal depressive symptoms (Barker, Jaffee, Uher, & Maughan, 2011; Kerr et al, 2013) or obstetric complications (Kerr et al, 2013). However, associations between prenatal maternal depressive symptoms and child emotional and behavioral problems are found to be genetically confounded (Gjerde et al, 2018; Hannigan et al, 2018), and the genetics of depressive symptoms is rather stable (Nes, Roysamb, Reichborn-Kjennerud, Harris, & Tambs, 2007). We can therefore assume that most of the potential prenatal influence is controlled for by the postnatal depressive symptoms included in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, it is possible that the associations between maternal depressive symptoms and child emotional and behavioral problems could be partly explained by various prenatal influences, such as maternal prenatal depressive symptoms (Barker, Jaffee, Uher, & Maughan, 2011; Kerr et al, 2013) or obstetric complications (Kerr et al, 2013). However, associations between prenatal maternal depressive symptoms and child emotional and behavioral problems are found to be genetically confounded (Gjerde et al, 2018; Hannigan et al, 2018), and the genetics of depressive symptoms is rather stable (Nes, Roysamb, Reichborn-Kjennerud, Harris, & Tambs, 2007). We can therefore assume that most of the potential prenatal influence is controlled for by the postnatal depressive symptoms included in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In the 2 publications using sibling-comparison designs, researchers found no significant associations in any of their reported analyses with offspring during early childhood (standardized b range, À.03 to .07). 51,59 As shown in Table 2, all effect sizes involving postnatal anxiety exposure were weak (standardized b and r range, .00 to .25). However, structural equation models in 2 publications using adoption designs showed that parent and child symptoms could prospectively predict one another across time, highlighting intergenerational, nongenetic, transactional effects during early and middle childhood.…”
Section: Additional Observationsmentioning
confidence: 94%
“…48,49 This could explain the relatively small effect sizes reported in the 2 sibling-comparison publications we included in meta-analyses. 51,59 It is also possible for both children-of-twins and sibling-comparison designs to overcorrect for genetic relatedness if genetic factors comprise an integral part of the causal pathway in parent-tochild environmental transmission, rather than acting as confounders across generations. 85 Further, in both designs, it is possible for the effects of evocative gene-environment correlation to inflate estimates of the parent's causal influence on the child.…”
Section: Considering the Role Of Methodological Confoundingmentioning
confidence: 99%
“…For example, children were at an increased risk of becoming teenage mothers if their mothers were teenagers at the time their first child was born ( Hardy et al, 1998 ), suggesting that age of parents at birth might be less important for intergenerational continuity of teenage parenthood than age of parent at birth of the first child in the family. Comparably, using a sibling comparison design, concurrent but not perinatal maternal depression was significantly associated with offspring internalizing and externalizing problems during preschool years ( Gjerde et al, 2017 ), and concurrent but not perinatal maternal anxiety was significantly associated with offspring internalizing problems ( Gjerde et al, 2020 ). Moreover, the effect of concurrent maternal depression on internalizing problems increased with child age.…”
Section: Methodological Considerations In Intergenerational Transmissmentioning
confidence: 99%